The Collaboration Between Space Form and Islamic Cultural Rituals on the Cultural Landscape Pattern of Cirebon City - Dini Rosmalia; Dhini Dewiyanti (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
There is a collaboration between spatial forms and Islamic (Javanese) cultural rituals in Cirebon city, which has the potential to shape the uniqueness of the cultural landscape. The research object is the Kanoman Sultanate which conducts the annual ritual, 'M(a)uludan' tradition. The aim is to describe the collaboration between the physical forms of the Keraton Kanoman and the M (a)uludan Tradition, which is the Islamic or Javanese culture. This involved using the qualitative description method through cultural participation for a period of 8 years. The results showed the existence of an imaginary space formation strung together by the presence of residents from 31 villages as followers (wargi) of the Keraton Kanoman. Moreover, the spatial form of the ritual route was discovered to have been formed for several generations. The people strongly believe that the presence and involvement of these routes can bring them virtue, blessings, prosperity, as well as protection from misfortune. This research argues that the imaginary space forms were created by these cultural events.